2012
DOI: 10.1038/nature11773
|View full text |Cite
|
Sign up to set email alerts
|

Centralspindlin links the mitotic spindle to the plasma membrane during cytokinesis

Abstract: At the end of cell division, cytokinesis splits the cytoplasm of nascent daughter cells and partitions segregated sister genomes. To coordinate cell division with chromosome segregation, the mitotic spindle controls cytokinetic events at the cell envelope. The spindle midzone stimulates the actomyosin-driven contraction of the cleavage furrow, which proceeds until the formation of a microtubule-rich intercellular bridge with the midbody at its centre. The midbody directs the final membrane abscission reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
158
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(170 citation statements)
references
References 44 publications
11
158
1
Order By: Relevance
“…PI(4,5)P2 interacts with the contractile ring components anillin and septins and regulates F-actin polymerization by modulating the activity of the actin-binding proteins profilin and cofilin (Yin and Janmey 2003;Bertin et al 2010;Liu et al 2012). Finally, recent studies have shown that the RhoGEF ECT2 and the centralspindlin subunit MgcRacGAP con-tain protein domains that bind to polyanionic phosphoinositide lipids (Su et al 2011;Frenette et al 2012;Lekomtsev et al 2012). Consistent with these observations, enrichment of PI(4,5) P2 is restricted to the cleavage furrow to maintain contractile ring structure (Ben El Kadhi et al 2011).…”
Section: Animal Cell Cytokinesismentioning
confidence: 99%
See 1 more Smart Citation
“…PI(4,5)P2 interacts with the contractile ring components anillin and septins and regulates F-actin polymerization by modulating the activity of the actin-binding proteins profilin and cofilin (Yin and Janmey 2003;Bertin et al 2010;Liu et al 2012). Finally, recent studies have shown that the RhoGEF ECT2 and the centralspindlin subunit MgcRacGAP con-tain protein domains that bind to polyanionic phosphoinositide lipids (Su et al 2011;Frenette et al 2012;Lekomtsev et al 2012). Consistent with these observations, enrichment of PI(4,5) P2 is restricted to the cleavage furrow to maintain contractile ring structure (Ben El Kadhi et al 2011).…”
Section: Animal Cell Cytokinesismentioning
confidence: 99%
“…4B), and its interaction with septins has been proposed to be required for the formation of these constrictions (Renshaw et al 2014). Finally, both anillin and the RacGAP component of centralspindlin have been shown to link directly the midbody ring to the plasma membrane (Kechad et al 2012;Lekomtsev et al 2012;Liu et al 2012).…”
Section: Animal Cell Cytokinesismentioning
confidence: 99%
“…Indeed, a second, smaller pool of centralspindlin that localizes to the plasma membrane has recently been shown to play a role (Basant et al 2015). The Cyk4 subunit of centralspindlin contains a weak membranebinding domain (Lekomtsev et al 2012). During anaphase, centralspindlin undergoes regulated oligomerization.…”
Section: Spindle-dependent Division-plane Positioning In Metazoamentioning
confidence: 99%
“…The mechanism of Aurora B localization is incompletely understood, although the kinesins of the Kif20 family (also called MKLP2) and Kif4 are required in vertebrate systems Nguyen et al 2014). Although the membrane-bound pool of centralspindlin is important when the midzone and cortex are far apart, in cells in which they are closer, or once the furrow has begun to ingress, in larger cells, the midzone pool of centralspindlin and associated ECT-2 likely sustain furrow ingression (Yüce et al 2005;Lekomtsev et al 2012). …”
Section: Spindle-dependent Division-plane Positioning In Metazoamentioning
confidence: 99%
See 1 more Smart Citation